2016
DOI: 10.1371/journal.pone.0154033
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cues of Object Properties Differentially Affect Anticipatory Planning of Digit Forces and Placement

Abstract: Studies on anticipatory planning of object manipulation showed initial task failure (i.e., object roll) when visual object shape cues are incongruent with other visual cues, such as weight distribution/density (e.g., symmetrically shaped object with an asymmetrical density). This suggests that shape cues override density cues. However, these studies typically only measured forces, with digit placement constrained. Recent evidence suggests that when digit placement is unconstrained, subjects modulate digit forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
8
2
Order By: Relevance
“…Both the handle-induced torques as well as previous external torques were higher correlated with T ΔCOP*GF than with T ΔLF*w/2 (Table S2) in separate models in which the torque components were the dependent variables. This finding stands in contrast with a recent study by Lee-Miller et al 2016 in which subjects failed to partition their finger positioning according to visual cues. We presume that the differences in the handle geometry and magnitude of the external torques account for this discrepancy as the handle was only half as wide as in the study by Lee-Miller et al 2016, whereas the maximal external torques were over three time as large.…”
Section: Reliance On Visual Geometric Cues For Anticipatory Torque Cocontrasting
confidence: 99%
See 3 more Smart Citations
“…Both the handle-induced torques as well as previous external torques were higher correlated with T ΔCOP*GF than with T ΔLF*w/2 (Table S2) in separate models in which the torque components were the dependent variables. This finding stands in contrast with a recent study by Lee-Miller et al 2016 in which subjects failed to partition their finger positioning according to visual cues. We presume that the differences in the handle geometry and magnitude of the external torques account for this discrepancy as the handle was only half as wide as in the study by Lee-Miller et al 2016, whereas the maximal external torques were over three time as large.…”
Section: Reliance On Visual Geometric Cues For Anticipatory Torque Cocontrasting
confidence: 99%
“…This finding stands in contrast with a recent study by Lee-Miller et al 2016 in which subjects failed to partition their finger positioning according to visual cues. We presume that the differences in the handle geometry and magnitude of the external torques account for this discrepancy as the handle was only half as wide as in the study by Lee-Miller et al 2016, whereas the maximal external torques were over three time as large. This could have necessitated anticipatory finger positioning to comfortably generate the required torques.…”
Section: Reliance On Visual Geometric Cues For Anticipatory Torque Cocontrasting
confidence: 99%
See 2 more Smart Citations
“…Bingham and Muchisky (1993) showed that humans can accurately judge the location of the COM using object symmetry. Lee-Miller et al (2016) have shown that an object's COM is judged from its visual appearance and that anticipatory planning of digit forces and placement is done on the basis of this visual estimate of the COM. Lederman and Wing (2003) showed that subjects actually grasp in such a way that the grasp axis (axis between the thumb and index finger) passes near or through the COM (also see Kleinholdermann et al 2007;Goodale et al 1994;Wing and Lederman 1998;Endo et al 2011).…”
Section: Introductionmentioning
confidence: 99%